Automatic Reading System of Scale Values on Webcam-Based Measuring Vessel - Budi Yasri; Gianto Gianto; Rossi Aulia Rachmawati (Publikasi Indonesia, 2024)
The fuel measurement pump is an installation used to measure the quantity of liquid fuel (BBM) to be sold or delivered to consumers. In the transaction of buying and selling fuel at gas stations, the fuel measurement pump plays a crucial role. Therefore, this measuring device needs to be calibrated or re-verified, and supervision is carried out using a standard measuring vessel with capacities of 10 L or 20 L. Errors in reading the measuring vessel can occur due to differences in individual visual acuity. To address this issue, a prototype for automatic reading of measuring vessels is created using a webcam camera. This prototype utilizes the Raspberry Pi 3 B+ as an image processor and the Logitech C270 webcam as an image capturer. The image processing process involves segmentation steps, transforming the image into a grayscale and then into a binary image. This research involves two different types of fluids in the volume measurement of the measuring vessel, namely distilled water (equates) and petalite. The measurement results with the prototype show an average accuracy level of around 99,23%, an average precision level of about 99,37%, and an average error rate of about 0,77%. For the equated fluid, the accuracy, precision, and error levels are 99,48%; 99.76%; and 0,52%, respectively. Meanwhile, for the petalite fluid, the accuracy, precision, and error levels are 98,98%; 98,80%; and 1,02%, respectively.